22q11 Deletion Syndrome and Urogenital Manifestations: A Clinicopathological Case Report - Vachette, M.; Grant, G. E.; Bouquet de la Joliniere, J.; Jotterand, M.; Ben Ali, N.; Feki, A.; Capoccia Brugger, R. (Frontiers in Medicine, 2016)
Background: Deletion in the chromosomal region 22q11 results from the abnormal development of the third and fourth pharyngeal pouches during embryonic life and presents an expansive phenotype with more than 180 clinical features described that involve every organ and system. History and Signs: A 23-year-old African woman presented for the first trimester echography, which revealed an isolated anechoic structure suggesting a ureteral dilatation. The suspicion of a malposition of great arteries in the second trimester indicated an amniocentesis leading to a diagnosis of 22q11 deletion. Outcome: At 32 weeks, the patient was admitted for premature rupture of membranes and gave birth 2 weeks later to a male newborn that presented a respiratory distress syndrome and probably died secondary to a tracheal stenosis. Necropsy revealed typical clinical features of 22q11 deletion associated with left renal agenesis, hypospadias and penile hypoplasia. Conclusions: We report a case of 22q11 deletion syndrome with typical clinical features associated with urogenital manifestations suspected at the first trimester ultrasound.